Incentivo à cultura de resultados: implantação do programa participação direta nos resultados no município de Santos - Raposo, Nelson (2014)
The municipality of Santos in search of innovation and modernity in public management decided to implement a variable compensation program with the participation of staff in the results of your folders. From the available material developed for its implementation, the theoretical framework of international and national experiences and interviews with leaders directly engaged in the process, this work is an interpretation of the positive and negative aspects of change present in this step in order to engage and enhance Santos has the servers and with the look of complicit public officials notes that can be used in the continuity of this program that represents a movement to stimulate positive change practices to service the population.